2005
DOI: 10.1111/j.1751-0813.2005.tb13325.x
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia due to Mycobacterium abscessus in two domestic ferrets (Mustelo putorius furo)

Abstract: Two ferrets were diagnosed with pneumonia due to Mycobacterium abscessus. Both cases were treated successfully using clarithromycin after positive cultures were obtained via unguided bronchoalveolar lavage. This is the first time M abscessus has been isolated in our laboratory and the first report of this organism causing disease in companion animals in Australia. Underlying respiratory tract disease was thought to be an important factor in the development of the infections. Thorough investigation of chronic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The most commonly reported infecting species is Mycobacterium bovis; however, M. avium complex (MAC) and M. triplex are also frequently isolated in New Zealand [4]. Reports of mycobacteriosis in domestic ferrets are sporadic [6, 7, 11, 13, 15, 16, 18] in other parts of the world. In Japan, the only report of mycobacteriosis in a domestic ferret was presented as a case report of suspected mycobacteriosis at an academic conference (The 29th Annual Meeting of Japanese Society of Clinical Veterinary Medicine).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The most commonly reported infecting species is Mycobacterium bovis; however, M. avium complex (MAC) and M. triplex are also frequently isolated in New Zealand [4]. Reports of mycobacteriosis in domestic ferrets are sporadic [6, 7, 11, 13, 15, 16, 18] in other parts of the world. In Japan, the only report of mycobacteriosis in a domestic ferret was presented as a case report of suspected mycobacteriosis at an academic conference (The 29th Annual Meeting of Japanese Society of Clinical Veterinary Medicine).…”
mentioning
confidence: 99%
“…Choice of and response to treatment vary depending on the species of mycobacterium [2, 7, 11, 13, 15, 16, 18, 19]. Macrolides, including clarithromycin and azithromycin, are generally effective for the treatment of most mycobacterium infections, whereas M. celatum is known to be resistant to rifampicin, and ciprofloxacin has been documented to be ineffective in the treatment of M. genavense.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Personnel at risk should be followed up by a physician for appropriate diagnostic testing (Fox, 1998a). While treatment is usually not recommended, in cases where survival of the animal is desired, management with clarithromycin (8-10 mg/kg PO, BID for 3 months) has been reported (Lunn et al, 2005 ) Therapy with rifampicin, clofazimine, and clarithromycin was reported in one publication to have potentially cured the infection in two affected animals (Lucas et al, 2000).…”
Section: Laboratory Animal Medicinementioning
confidence: 99%
“…25 The use of antipyretic drugs to control fever is of questionable merit because fever is an important host defense mechanism. 12,32,50,61 Gram-negative bacteria such as Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa have been isolated from ferrets. 26 In a recent meta-analysis of the use of antipyretics in animal models of influenza virus, risk of mortality increased with the use of antipyretics (aspirin, paracetamol, and diclofenac).…”
Section: Treatmentmentioning
confidence: 99%